2012
DOI: 10.1002/jctb.3818
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced saccharification of corn straw pretreated by alkali combining crude ligninolytic enzymes

Abstract: BACKGROUND: This work investigated the monokaryogenesis of dikaryon strains of Trametes hirsuta by protoplasts regeneration for extracellular ligninolytic enzyme production. Saccharification of corn straw was enhanced by alkali pretreatment combining crude ligninolytic enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 58 publications
2
13
1
Order By: Relevance
“…50%) by SEC analysis 8% increment of glucose production [112] Alkali-extracted corn straw Trametes hirsuta Increment of porositiy and surface area in laccase-treated samples 2-fold increment in sugar production [113] Alkali-extracted straw from Brassica campestris Ganoderma lucidum…”
Section: Four Cycles Of Myceliophthora Thermophila Laccase -Alkaline mentioning
confidence: 99%
See 1 more Smart Citation
“…50%) by SEC analysis 8% increment of glucose production [112] Alkali-extracted corn straw Trametes hirsuta Increment of porositiy and surface area in laccase-treated samples 2-fold increment in sugar production [113] Alkali-extracted straw from Brassica campestris Ganoderma lucidum…”
Section: Four Cycles Of Myceliophthora Thermophila Laccase -Alkaline mentioning
confidence: 99%
“…Properties such as porosity, surface area, and hydrophobicity can be altered, resulting in the reduction of unproductive binding of hydrolases. Li et al [113] observed an increment in the porosity and surface area of alkali-extracted corn straw after a treatment with Trametes hirsuta laccase, doubling the sugar production. The same effect was observed on alkali-extracted straw from Brassica campestris [114].…”
Section: Pretreated Materials Laccase Treatment Effects Observed Benefmentioning
confidence: 99%
“…Delignification assays can be performed at up to a liquid:solid ratio of 2:1, and it is customary to use solid charges in a ratio of (20:1 or less) . The enzymes added can vary between 4000 and 80 000 IU/g . Enzymatic delignification combined with other pretreatment technologies (as microbial delignification) to make it more effective.…”
Section: Organic Solventsmentioning
confidence: 99%
“…Ligninolytic enzymes as shown in Table are successfully used for a number of industrial applications, such as, organic compound manufacturing, polymer reformation, and removal of environmental toxins . The use of laccases to remove lignin was successfully applied to improve enzymatic hydrolysis . In the case of laccase enzyme, a suitable redox mediator must be present to stabilize in its redox states, and it should not inhibit the catalytic activity .…”
Section: Organic Solventsmentioning
confidence: 99%
See 1 more Smart Citation